The Impact of Commitment-Based Human Resources Practices on Psychological Well-Being by Mediating Passion for Work. An Analytical Study of The Viewpoints of a Sample of Workers at The Holy Karbala Education Directorate - Alwan, Bushra Mohammed (Research Parks Publishers, 2024)
The research aims to explore the mediating role of passion for work in strengthening the relationship between adopting commitment-based human resources practices and achieving psychological well-being among workers in the Holy Karbala Education Directorate. The field of research, as the intellectual problem of the research, was represented by the central question: Does adopting commitment-based human resources practices in the Directorate contribute to... Raising the Holy Karbala in enhancing psychological well-being through the mediating role of passion for work? The research was applied in the Holy Karbala Education Directorate on a random sample of (196) respondents from workers in the studied directorate using a questionnaire form that was designed specifically for this project. Through the utilization of SPSS V AMOS 24.26, a collection of statistical techniques, such as structural equation modeling and path analysis, were utilized in order to conduct the analysis of the data. The researcher reached a set of conclusions, the most important of which is the existence of a correlation and direct, significant influence between the research variables, as well as the presence of an indirect, significant influence of passion for work in the relationship between adopting human resources practices based on commitment and enhancing psychological well-being among workers in the studied directorate. Therefore, on the basis of the findings that the researcher obtained, she was able to formulate a number of recommendations to improve levels of response to work requirements, the most important of which are establishing written, clear and precisely defined recruitment and appointment procedures, the Directorate’s reliance on various training programs in line with the variables of the global environment, and the necessity of the Directorate granting incentives and rewards to employees based on Established standards, as well as the need to continuously develop the incentives and rewards system in the directorate